Online Loan Regulation in Indonesia: Challenges and Solutions for the Community - Sutawijaya, Darmawan (Socious Journal, 2025)
The development of financial technology in Indonesia has driven the growth of online lending services (fintech lending) as an alternative source of funding that is easily accessible to the public. However, behind its benefits, various challenges have emerged, such as the rise of illegal online loans, weak consumer protection, and the increasing risk of default. The regulations implemented by the Financial Services Authority (OJK) and related agencies aim to regulate and supervise these services so that they continue to run in accordance with healthy and fair financial principles. This study discusses the main challenges in implementing online lending regulations, including low financial literacy among the public, unethical collection practices, and limitations in supervision and law enforcement. In addition, this study also outlines various solutions that can be implemented, such as tightening regulations, improving financial education, strengthening data security technology, and providing safer funding alternatives for the public. In conclusion, the success of online lending regulations is highly dependent on the synergy between the government, financial institutions, and the public in creating a more transparent, safe, and beneficial lending ecosystem for the national economy. With the strengthening of regulations and higher public awareness, it is hoped that fintech lending can develop healthily without harming users.